PELAKSANAAN PERATURAN DAERAH KOTA DENPASAR NOMOR 24 TAHUN 2001 TENTANG USAHA HOTEL MELATI DI KOTA DENPASAR - Rudi Darmika, I Putu; R., Ibrahim; Suharta, I Nengah (Kertha Negara : Journal Ilmu Hukum, 2014)
Implementation of tourism accommodation activities pertaining to non-star hotel business at first have been regulated by office of tourism Denpasar city, but as the emergence of office of licensing, and occurring transition to the monitoring task of non-star hotel business. Where all the implementation of and supervision over non-star hotel business now governed by office of licensing local regulations number of 24/2001 on non-star hotel business. It is causing the occurrence of problem where there are many non-starhotel business who commits an offense against business permit such as : many non-star hotel business who no license, and many non-star hotel business which is not extend the license, and many non-star hotel business that has changed ownership, but not registered it and there is also a non-star hotel business which have previously been registered in tourism agency, but after it has occurred transition the effort is not registered back. This article uses empirical legal research. From the description above then can be concluded that the implementation of and supervision over non-star hotel business in the city of denpasar still not fit with local regulation number of 24 / 2001 on nonstar business.
Keywords: Business License, Supervision, Non-Star Hotels